Acúmulo de massa seca na soja em resposta a aplicação foliar com silício sob condições de déficit hídrico - Teodoro, Paulo Eduardo; Ribeiro, Larissa Pereira; de Oliveira, Elisa Pereira [UNESP]; Corrêa, Caio Cezar Guedes; Torres, Francisco Eduardo (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2015)
The foliar fertilization with silicon has promoted several actions beneficial to plants, among them is greater drought tolerance, however, for the soybean, there is little information on these benefits in this condition. Thus, the aim of this study was to evaluate the effect of silicon on leaf, the dry matter accumulation of soybean in their reproductive stages, where the crop water stress suffered during the same. The experiment was carried out at the Plant Science Unit Aquidauana University - State University of Mato Grosso do Sul. The statistical design was a randomized block split plot with four replications. The plots were represented by cultivar 5DR615, the subplots consisted of the application (with or without) silicon, whose source was used KSi. Was measured the height and identified the development stage of all plants, separating them into stem + branches, leaves + petioles, pods capsules and seed. Foliar applications of silicon increased dry matter accumulation during the reproductive stage of soybean, where the highest values occurred in the R6 stage. Under conditions of water deficit, foliar application of silicon on soybean provided normal plant development, generating greater dry mass of stem + branches, leaves + petioles, pods capsules and seeds throughout their reproductive phase, with the highest values obtained at R6 stage (35 days after R2).
Dry mass in soybean in response to application leaf with silicon under conditions of water deficit
Keywords: Dry mass air; Foliar fertilization; Glycine max; Water stress